Legal Study on the Crime of Defamation through social media according to Law Number 19 of 2016 concerning Information and Electronic Transactions - Warsiman Warsiman; Indra Gunawan Purba; Syapri Can (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The current era of globalization is marked by the development of information and electronic communication technology that affects people's lifestyles, one of these technological developments is social media. The consequences of the development of information technology are quite diverse, because users who cannot be limited by space and time are therefore said to be a double-edged sword. The positive consequences of the development of information technology include making it easier for humans to get information, share information, express themselves, and so on. Meanwhile, the negative consequences of the development of information technology are fraud, kidnapping, online gambling, human trafficking, prostitution, humiliation, and even defamation. The development of this technology has a significant influence on the understanding of crime, especially on the streams of criminology which focuses on the human factor both physically and psychologically. One of the crimes that often occurs in the development of information and communication technology is humiliation or defamation carried out through social media which is regulated in Article 310 and Article 311 of the Criminal Code. In addition, defamation through social media is also regulated in Article 27 paragraph (3) of Law Number 11 of 2008 in conjunction with Law Number 19 of 2016 concerning Electronic Information and Transactions.